The symbolism of the banners and their significance in Islamic history - عباس, بشار (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Banners have been known since ancient times to most peoples, and were used by the Assyrians, the Pharaohs, the Romans, and others. The Arabs used to consider the flags as a symbol of the army and its strength in wars, and the shapes, sizes and colors of these flags varied, and they were given many general names such as the brigade, the flag, and other terms that indicate a class, group, battalion, or army, in addition to special names such as Al-Aqab, Al-Jumah, and others, and the flag was a symbol For the center of command or weight, it is often in the hands of the bravest knights or commanders, and its fall means losing the battle. The banners continued to be raised in wars after the advent of Islam as well, and it was reported from the Prophet that he used the banner in his conquests, and he had more than one banner in several colors and shapes. The Islamic armies were divided into several sections, and sometimes there were several small banners in one army in addition to the large banner, and with the passage of time the banner became a symbol to distinguish one group from another. Thus, each state has a flag with which it is known, and a color that distinguishes it from other flags and flags, and sometimes phrases and shapes that have symbolism and multiple connotations.